2018
DOI: 10.1073/pnas.1720475115
|View full text |Cite
|
Sign up to set email alerts
|

Family with sequence similarity 13, member A modulates adipocyte insulin signaling and preserves systemic metabolic homeostasis

Abstract: Adipose tissue dysfunction is causally implicated in the impaired metabolic homeostasis associated with obesity; however, detailed mechanisms underlying dysregulated adipocyte functions in obesity remain to be elucidated. Here we searched for genes that provide a previously unknown mechanism in adipocyte metabolic functions and identified family with sequence similarity 13, member A (Fam13a) as a factor that modifies insulin signal cascade in adipocytes. Fam13a was highly expressed in adipose tissue, predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…Many previous papers reported a critical role of WAT insulin signaling in the regulation of systemic metabolic homeostasis 48,49 . Furthermore, it has been reported that enhancing insulin signaling in adipocytes is sufficient to improve systemic metabolic homeostasis, while impaired insulin signaling in adipocytes causes systemic metabolic disorders 50,51 . Therefore, adipocyte senescence induces systemic metabolic disorders at least partially through impairing fat insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous papers reported a critical role of WAT insulin signaling in the regulation of systemic metabolic homeostasis 48,49 . Furthermore, it has been reported that enhancing insulin signaling in adipocytes is sufficient to improve systemic metabolic homeostasis, while impaired insulin signaling in adipocytes causes systemic metabolic disorders 50,51 . Therefore, adipocyte senescence induces systemic metabolic disorders at least partially through impairing fat insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genome-wide association studies suggest a strong association between FAM13A and chronic lung diseases. FAM13A is expressed in various types of tissues and cells, including airway and alveolar epithelial cells in the lung, pulmonary vascular cells, and mature adipocytes in adipose tissue [10,11,24]. Accordingly, FAM13A has been involved in multiple biological processes such as epithelial cell regeneration, tumor cell proliferation and survival, and insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…FAM13A interacts with protein phosphatase 2A and β-catenin, leading to the promotion of GSK-3β-mediated phosphorylation and subsequent proteasomal degradation of β-catenin in airway epithelial cells [10]. Interestingly, FAM13A is also expressed in adipocytes, and modulates insulin signaling through regulating the proteasomal degradation of insulin receptor substrate-1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…FAM13A also has two coiled-coil domains that often play a role in the protein-protein interaction. Indeed, FAM13A binds to insulin receptor substrate-1 in a coiled-coil domain-dependent manner, while it binds to protein phosphatase 2A (PP2A) independently of their coiled-coil domain [11]. Other study in COPD has revealed the importance of interaction between FAM13A and PP2A in bronchial epithelial cells that leads to β-catenin degradation through GSK3β-mediated phosphorylation, although the coiled-coil domain dependency is not clear [10].…”
Section: Discussionmentioning
confidence: 99%
“…FAM13A interacts with protein phosphatase 2A and β-catenin, leading to the promotion of GSK-3β-mediated phosphorylation and subsequent proteasomal degradation of β-catenin in airway epithelial cells [10]. Interestingly, FAM13A was also expressed in adipocytes, and modulates insulin signaling through regulating the proteasomal degradation of insulin receptor substrate-1 [11].…”
Section: Introductionmentioning
confidence: 99%